ETHICAL LEADERSHIP BASED ON VUDDHIDHAMMAS FOR SCHOOL ADMINISTRATORS IN THE 4.0 ERA - Panphet, Gunchaporn (Journal of Educational Review Faculty of Education in MCU, 2022)
Ethical Leadership based on Vuddhidhammas for School Administrators in the 4.0 Era is an administration that relies on the role of school administrators that demonstrate leadership in schools on the aspects of aware of change, being a thinker and a developer. They also have a vision in management that is ready for change, democratic administration by receiving other people's opinions, share ideas, work together, and solve problems with personnel in the organization. Developed using new innovations by considering the elements of ethical leadership are also conducted in order to be consistent with the important Buddhist way of life. The key aspects are 1) Justice, 2) Power Cooperation, 3) Functional Clarity, 4) People Focus, 5) Ethical Guidance, 6) sustainability, and 7) Integrity. It is a moral and ethical principle that is appropriate to the principles of morality which is Dharma of a growth tool and is a virtue that leads to prosperity in 4 things: 1) Sappurisangseva is the fellowship of the wise; 2) Saddhammassavana, listening to the true Dhamma and pay attention to study and find out the truth; 3 Yonisomanasikarn, mindfulness to think of reasons in the right way; 4) Dhammanudhamma practice, Dharma practice according to the principles in order to develop educational institutions to be ready for changes according to globalization and in the 4.0 era.